Caracterização óptica de suspensões de nanotubos de carbono de parede única quiralmente enriquecidas por cromatografia - Rafael Nunes Gontijo (2015)
Single Wall Carbon Nanotubes (NTs) have the interesting property of being both metallic and semiconducting, depending uniquely on its geometric characteristics (diameter and chirality). Any NT production process has a large diameter distribution, which can be a hindering for its possible applications in which it is necessary that the electronic character of the NTs is well defined. In this context, separation techniques for sorting the NTs have been developed. Two of these that can be highlighted are the density gradient ultracentrifugation (DGU) and the column chromatography, technique based in the electronic affinity between NTs species and the column medium, was used in this work for obtaining separated and enriched samples of NTs. The focus of this work is the optical characterization of the separated samples combining both Raman spectroscopy and optical absorption. By means of RamanSpectroscopy, it is possible to obtain the relative concentration among the NTs species in the separated samples by the analysis of the Raman excitation profile for the radial breathing mode (RBM). This is a characteristic Raman mode for each NT species for its relation with the NT diameter. Along with the optical absorption, these data provide theabsolute concentration of the species present in the sample. From these data, it was observed that (6,5) enriched NT samples can reach an enrichment of 60% of this species in the relative concentration and (7,6) enriched NT samples can reach an enrichment of nearly 80%.Combining both techniques, a simple and trustworthy method for characterizing the separated samples is achieved, for it is possible to see the individual contribution of each species for the sample, which enables the characterization of other NTs dispersions.